Galilean invariance study on different lattice Boltzmann fluid–solid interface approaches for vortex-induced vibrations. (1st September 2020) - Haussmann, Marc; Hafen, Nicolas; Raichle, Florian; Trunk, Robin; Nirschl, Hermann; Krause, Mathias J.
Abstract: The present work compares fluid–solid interface approaches for the lattice Boltzmann method (LBM) to study vortex-induced vibrations (VIV). Two classes of fluid–solid interface approaches, namely the partially saturated methods (PSM) (Noble and Torczynski (1998), Holdych (2003), Krause et al. (2017), Trunk et al. (2018)) and moving boundary methods (MBM) (Bouzidi et al. (2001), Lallemand and Luo (2003), Yu et al. (2003), Ginzburg et al. (2008) and Filippova and Hänel (1998), Mei et al. (1999, 2000)), are investigated. First, the Galilean invariance of aerodynamic coefficients obtained by each scheme is examined. The Bhatnagar–Gross–Krook (BGK) LBM is utilized to simulate an eccentrically positioned cylinder in a transient Couette flow. In addition, various refill methods for MBM and volume approximation techniques for PSM are tested. Besides different error norms and a grid independence study of each method, the Galilean invariance violating frequencies are studied as well. These error calculations are used to choose a representative for each class to simulate vortex shedding. The VIV test case describes a transverse oscillation of a cylinder in a freestream at a Reynolds number of 100. Both free and forced cylinder oscillations are examined to study known phenomena as lock-in and lock-out zones. The results of MBM and PSM are in good agreement to literature values and prove the suitability for VIV simulations.